2018
DOI: 10.1016/j.bbi.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Dietary omega-3 deficiency exacerbates inflammation and reveals spatial memory deficits in mice exposed to lipopolysaccharide during gestation

Abstract: Maternal immune activation (MIA) is a common environmental insult on the developing brain and represents a risk factor for neurodevelopmental disorders. Animal models of in utero inflammation further revealed a causal link between maternal inflammatory activation during pregnancy and behavioural impairment relevant to neurodevelopmental disorders in the offspring. Accumulating evidence point out that proinflammatory cytokines produced both in the maternal and fetal compartments are responsible for social, cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 152 publications
1
58
1
Order By: Relevance
“…At high levels of DHA and EPA, AA becomes suppressed (125), and correlation between low levels of AA and poor growth have been demonstrated (126). Rodent models of neonatal brain injury have demonstrated neuroprotective effects of DHA through several potential mechanisms (27,127,128). Labrousse et al demonstrated association between n-3 fatty acid deficiency and increased levels of cytokines (127).…”
Section: Discussionmentioning
confidence: 99%
“…At high levels of DHA and EPA, AA becomes suppressed (125), and correlation between low levels of AA and poor growth have been demonstrated (126). Rodent models of neonatal brain injury have demonstrated neuroprotective effects of DHA through several potential mechanisms (27,127,128). Labrousse et al demonstrated association between n-3 fatty acid deficiency and increased levels of cytokines (127).…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Inflammation is recognized to associate with various aspects of cardiovascular disease. [23][24][25] Inflammation is recognized to associate with various aspects of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanistic pathways by which these nutrients may affect ASD is not clear, it has been hypothesised that the relationship between these nutrients and ASD can be partly mediated by inflammatory markers, as seen in other neuropsychiatric conditions where inflammation may contribute [46][47][48]. To the best of our knowledge, no studies have examined the potential modifying effect of participants' pre-treatment inflammatory state on vitamin D and omega-3 LCPUFA treatment response in children with ASD.…”
Section: Introductionmentioning
confidence: 99%